2009
DOI: 10.1038/ajg.2009.186
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Transcatheter Embolotherapy for Acute Lower Gastrointestinal Hemorrhage

Abstract: Transcatheter embolotherapy to treat lower gastrointestinal bleeding is very effective, with a relatively low rebleeding and ischemic complication rate, mostly occurring within the first month after the embolization. Long-term follow-up shows a very low late rebleeding rate, and half of the embolized patients survive more than 5 years. This study shows that the majority of patients presenting with lower gastrointestinal bleeding, unresponsive to endoscopic therapy, do not benefit from transcatheter embolizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 22 publications
8
53
0
Order By: Relevance
“…Other authors found that presence of more than one comorbid condition was associated with increased overall mortality (12,13). Our technical success, clinical success, and rebleeding rates in patients with positive angiograms are similar to those published in other studies (3,(6)(7)(8). Tachycardia at first presentation was a predictor of both 30-day and overall mortality.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Other authors found that presence of more than one comorbid condition was associated with increased overall mortality (12,13). Our technical success, clinical success, and rebleeding rates in patients with positive angiograms are similar to those published in other studies (3,(6)(7)(8). Tachycardia at first presentation was a predictor of both 30-day and overall mortality.…”
Section: Discussionsupporting
confidence: 78%
“…Surgery for lower GI bleeding is usually reserved for patients with uncontrollable bleeding and failed angiographic embolization, or postembolization ischemic bowel complications (6,15). We did not encounter major complications in the 120 procedures in our study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…[19][20][21] However, it requires specialized equipment and experienced interventional radiologists, preventing its widespread access beyond large centres. It has been shown, albeit in retrospective studies only, to be at least as equally effective as surgery after endoscopic failure for acute UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic embolotherapy is considered to be a salvage therapy with reported technical success rates of 69-100% and rebleeding rates of 10-30% within 30 days of initial application [Luchtefeld et al 2000;Weldon et al 2008]. A major adverse event of embolotherapy is the increased risk of bowel ischemia or infarct after arterial embolization, which has been reported to range from 0% to 22% [Maleux et al 2009].…”
Section: Introductionmentioning
confidence: 99%